The opsin genes of amazonian cichlids - Escobar-Camacho, Daniel; Ramos, Erica [UNESP]; Martins, Cesar [UNESP]; Carleton, Karen L. (Wiley-Blackwell, 2017)
Vision is a critical sense for organismal survival with visual sensitivities strongly shaped by the environment. Some freshwater fishes with a Gondwanan origin are distributed in both South American rivers including the Amazon and African rivers and lakes. These different habitats likely required adaptations to murky and clear environments. In this study, we compare the molecular basis of Amazonian and African cichlid fishes' visual systems. We used next-generation sequencing of genomes and retinal transcriptomes to examine three Amazonian cichlid species. Genome assemblies revealed six cone opsin classes (SWS1, SWS2B, SWS2A, RH2B, RH2A and LWS) and rod opsin (RH1). However, the functionality of these genes varies across species with different pseudogenes found in different species. Our results support evidence of an RH2A gene duplication event that is shared across both cichlid groups, but which was probably followed by gene conversion. Transcriptome analyses show that Amazonian species mainly express three opsin classes (SWS2A, RH2A and LWS), which likely are a good match to the long-wavelength-oriented light environment of the Amazon basin. Furthermore, analysis of amino acid sequences suggests that the short-wavelength-sensitive genes (SWS2B, SWS2A) may be under selective pressures to shift their spectral properties to a longer-wavelength visual palette. Our results agree with the sensitivity hypothesis' where the light environment causes visual adaptation. Amazonian cichlid visual systems are likely adapting through gene expression, gene loss and possibly spectral tuning of opsin sequences. Such mechanisms may be shared across the Amazonian fish fauna.
Keywords: Amazon; cichlids; fish vision; opsins